Automated System for OEE Management in the Industrial Sector (2025)
In today’s fast-paced manufacturing environment, the need to monitor production processes is becoming increasingly urgent. As companies strive to remain competitive in the Industry 4.0 era, they seek innovative solutions to enhance efficiency. This project addresses that need by providing a solution to capture OEE (Overall Equipment Effectiveness) measurements from machines in the drum-filling industry, specifically targeting semi-automatic equipment. The primary objective is to streamline decision-making and improve data management performance. In collaboration with Alianza Team S.A., this article outlines the detailed design and development process of a web platform called AutOEE, which integrates the Snap7 communication technology. Additionally, the article presents technical experiments, including tests conducted using a PLC provided by ELEIA to simulate real production environments. These tests verified system stability, web interface responsiveness, and accurate data extraction, with reconnection features to recover from connectivity loss. The platform also supports real-time and historical OEE data visualization, with customizable views for specific days and shifts. User feedback, gathered through a web interface test with randomized data, was overwhelmingly positive (98%), praising ease of use, relevance, and load times. However, suggestions for improvement included simplifying access to historical data, adding PDF report generation, improving security, and enhancing error reporting. These insights will guide future platform updates.